Modern Challenges in Developing Special Endurance Qualities in Female Volleyball Players (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article analyzes modern problems of developing the quality of special endurance in female volleyball players and offers scientifically based solutions. The article examines the main obstacles to the development of special endurance in women's volleyball in Uzbekistan, including the lack of scientific methods, physiological and psychological factors, infrastructure and financial problems. Solutions such as the use of modern technologies, strengthening psychological training, and improving the qualifications of coaches are also proposed. The article emphasizes the importance of cooperation between the state, sports organizations, and the scientific community in the development of women's sports.